A review of heavy metals in coastal surface sediments from the red sea: health-ecological risk assessments - Al-Mutairi, Khalid Awadh; Yap, Chee Kong (Multidisciplinary Digital Publishing Institute, 2021)
The heavy metal (HM) pollution in sediment is of serious concern, particularly in the Red Sea environment. This study aimed to review and compile data on the concentrations of four HMs (Cd, Cu, Pb, and Zn) in the coastal surface sediments from the Red Sea, mainly from Saudi Arabia, Egypt, and Yemen, published in the literature from 1992 to 2021. The coastal sediments included those from mangrove, estuaries, and intertidal ecosystems. It was found that the mean values of Cd, Cu, Pb, and Zn in coastal Red Sea sediments were elevated and localized in high human activity sites in comparison to the earth upper continental crust and to reference values for marine sediments. From the potential ecological risk index (PERI) aspect, 32 reports (47.1%) were categorized as ‘considerable ecological risk’ and 23 reports (33.8%) as ‘very high ecological risk’. From the human health risk assessment (HHRA) aspect, the non-carcinogenic risk (NCR) values (HI values < 1.0) of Cd, Cu, Pb, and Zn represented no NCR for the ingestion and the dermal contact routes for sediments from the Red Sea countries. The reassessment of the HM data cited in the literature allowed integrative and accurate comparisons of the PERI and HHRA data, which would be useful in the management and sustainable development of the Red Sea area, besides being a helpful database for future use. This warrants extensive and continuous monitoring studies to understand the current and the projected HM pollution situation and to propose possible protective and conservative measures in the future for the resource-rich Red Sea ecosystem.